Autophagy: A Double-Edged Sword to Fight Plant Viruses. (August 2017) - Clavel, Marion; Michaeli, Simon; Genschik, Pascal
Abstract : In metazoans, autophagy is an essential component of host defense against viruses, orchestrating their degradation. Such antiviral functions for autophagy have also been long suspected in the green lineage. Two recent reports provide molecular insights on how plants selectively send viral proteins and even particles to the vacuole.